2015
DOI: 10.1016/j.yfrne.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal control of gonadotropin-inhibitory hormone (GnIH) in birds and mammals

Abstract: Animals inhabiting temperate and boreal latitudes experience marked seasonal changes in the quality of their environments and maximize reproductive success by phasing breeding activities with the most favorable time of year. Whereas the specific mechanisms driving seasonal changes in reproductive function vary across species, converging lines of evidence suggest gonadotropin-inhibitory hormone (GnIH) serves as a key component of the neuroendocrine circuitry driving seasonal changes in reproduction and sexual m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 106 publications
(98 citation statements)
references
References 129 publications
(170 reference statements)
3
93
0
2
Order By: Relevance
“…Recently interest has turned somewhat towards GnIH which, as its name implies, has inhibitory effects upon gonadotropin secretion although the degree to which these are critical in the major changes during seasonal breeding in birds and mammals remains unresolved. Kriegsfeld et al (2015) summarize the results and offer arguments as to how this antagonist action of GnIH is involved in the control of reproduction.…”
Section: But Seasonality Is Far More Than Reproduction!mentioning
confidence: 95%
See 1 more Smart Citation
“…Recently interest has turned somewhat towards GnIH which, as its name implies, has inhibitory effects upon gonadotropin secretion although the degree to which these are critical in the major changes during seasonal breeding in birds and mammals remains unresolved. Kriegsfeld et al (2015) summarize the results and offer arguments as to how this antagonist action of GnIH is involved in the control of reproduction.…”
Section: But Seasonality Is Far More Than Reproduction!mentioning
confidence: 95%
“…Our understanding of how thyroidectomy changed refractoriness has changed since the 1980s but its value in allowing the separation of the overall photoperiodic response into two components remains unaltered. One is called "photo-induction" by Dawson (2015) with long days stimulating the neuroendocrine axis to secrete GnRH and probably other hormones too such as prolactin and Gn-IH (Ebling, 2015;Kriegsfeld et al, 2015). This is the "classical" response and the rate of photoinduction is proportional to day length.…”
Section: Refractorinessmentioning
confidence: 99%
“…In 2000, we provided a new concept on the basis of the discovery of gonadotropin-inhibitory hormone (GnIH), a hypothalamic neuropeptide that actively reduces gonadotropin release, in quail (Tsutsui et al, 2000a). The follow-up studies demonstrated that GnIH is highly conserved among vertebrates, from agnathans to humans, and that it acts as a key player for regulation of reproduction (for reviews, see Kriegsfeld et al, 2015;Tsutsui, 2009;Tsutsui and Ubuka, 2012;Tsutsui and Ukena, 2006;Tsutsui et al, 2006bTsutsui et al, , 2007Tsutsui et al, , 2010aTsutsui et al, ,b, 2012bTsutsui et al, , 2013dUkena and Tsutsui, 2005). In addition, recent studies have demonstrated that GnIH has other important functions beyond reproduction Ubuka et al, 2014).…”
Section: Overviewmentioning
confidence: 99%
“…It now appears that GnIH acts on the pituitary and the brain to serve a number of behavioral and physiological functions other than regulation of reproduction. Thus, following 14 years of GnIH research in collaboration with the laboratories of Wingfield, Bentley, Kriegsfeld, Clarke, Sower, and others has obtained new insights in the field of neuroendocrinology (for reviews, see Kriegsfeld et al, 2015;Tsutsui, 2009;Tsutsui and Ubuka, 2012;Tsutsui et al, 2006bTsutsui et al, , 2007Tsutsui et al, , 2010aTsutsui et al, ,b, 2012bTsutsui et al, , 2013dUbuka et al, 2013).…”
Section: Overviewmentioning
confidence: 99%
“…Gonadotropin-inhibitory hormone (GnIH) (Tsutsui et al, 2000), which inhibits both LH release from the pituitary gland and GnRH cells directly (for reviews, see Clarke, 2011;Kriegsfeld et al, 2015;Tsutsui, 2009;Tsutsui et al, 2010Tsutsui et al, , 2012, is one potential candidate in this mediation. Short-term energy deprivation stimulates GnIH activity in the Pekin duck, Anas platyrhynchos domestica (Fraley et al, 2013), and GnIH can stimulate food intake in birds and mammals (for reviews, see Clarke et al, 2012;Kriegsfeld et al, 2015;Tsutsui, 2009;Tsutsui et al, 2010Tsutsui et al, , 2012. Neuropeptide Y (NPY) is another neuropeptide that may be involved in transducing metabolic information to GnRH cells.…”
Section: Introductionmentioning
confidence: 99%